Systematic revision of Nacella (Patellogastropoda: Nacellidae) based on a complete phylogeny of the genus, with the description of a new species from the southern tip of South America - Gonzalez-Wevar, Claudio A.; Hune, Mathias; Rosenfeld, Sebastian; Nakano, Tomoyuki; Saucede, Thomas; Spencer, Hamish; Poulin, Elie (My University, 2019)
True limpets of the genus Nacella (Patellogastropoda: Nacellidae) include at least 11 nominal species distributed in different provinces of the Southern Ocean. Here, we present new molecular analyses and a comprehensive morphological revision of Nacella confirming the validity of all the currently recognized species, but with important amendments to the published distributions of several. We also show that specimens collected along two fjords in the Beagle Channel, southern South America, constitute a new taxon: Nacella yaghana sp. nov. The phylogenetic position of this new taxon in our molecular tree reveals that it represents an ancestral South American lineage of Nacella, markedly separated from the previously recognized and evolutionary recent Magellanic radiation. In addition, this new Nacella species was clearly distinguished from the rest of the species by morphological comparisons, including shell characteristics, radular-tooth shape and configuration, as well as by the coloration pattern of the mantle tentacles. This study provides new evidence about the evolutionary history of this important Southern Ocean, marine, near-shore benthic group and the role of the Antarctic Circumpolar Current in the biogeography of the genus.
Keywords: antarctica; biogeography; coi mtdna; miocene; molecular phylogeny; mollusca; morphology; patagonia; phylogenetic systematic; rrna